MAKNA KOSAKATA GHARĪB AL-QUR’AN DALAM KITAB AL-‘UMDAH KARYA MAKKĪ AL-QAISĪ - Karimah, Hasna Iffah (Department of Ilmu al-Qur'an dan Tafsir, Faculty of Ushuluddin and Adab, State Islamic University of Sultan Maulana Hasanuddin Banten, Indonesia, 2022)
The Al-Qur'an was revealed by Allah SWT in Arabic according to the language of the Prophet Muhammad and the Arab population. However, there are several opinions that the Qur'an contains languages ​​other than Arabic. This was the talk of the Muslims at that time, because the Al-Qur'an was revealed in Arabic, where there could be no mixing of other languages. So this led to the emergence of Islamic studies on the science of gharib Al-Qur'an which discusses the meaning of a recitation of the Qur'an that is difficult to understand. Basically Arabs understand the languages ​​of every tribe that is there, even though the tribes are different, there must be some words that have something in common, even if only a little. If there are different words, then this is what makes the other tribes not understand the sentences spoken by other tribes. The surah which is the object of research here is Yāsīn's surah. Where Yāsīn's surah is a well-known letter among the people. This study uses a comparative method, in which the researcher uses al-'Umdah fī Gharīb Al-Qur'ān by Imam Makkī as a reference for gharīb classification and then looks at how it is interpreted in the book of interpretations of Jāmi' Al-Bayān fī Ta'wīl Al-Qur'ān by Ibn Jarir Al-ṭabāri, then compares the interpretation of the two book.